2006
DOI: 10.1108/19852510680001585
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Factors in Organizational Change Process: Observations from the Perspective of Management Accounting

Abstract: Worldwide efforts to transform the public sector under the theme of 'New Public Management' have been concerned with the issues of organizational change management. The change in the Accounting sector is one of the pillars of such efforts. This paper promotes the importance of leadership roles within the accounting change process by studying them within the context of a corporatized public sector entity. It offers a longitudinal analysis (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) through the framework of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In this context, we formulate the following hypothesis: H4: The utility that manager attributes to FI influences economic company performance. Mail et al (2006), Biancone et al (2019) and Janka et al (2020) discuss the importance of studying change management accounting practice that could lead to improve organizational innovation and performance. Mail et al (2006) demonstrated that management accounting, as a managerial tool in creating organizational control, has a positive effect on organizational, financial, and operational performance.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, we formulate the following hypothesis: H4: The utility that manager attributes to FI influences economic company performance. Mail et al (2006), Biancone et al (2019) and Janka et al (2020) discuss the importance of studying change management accounting practice that could lead to improve organizational innovation and performance. Mail et al (2006) demonstrated that management accounting, as a managerial tool in creating organizational control, has a positive effect on organizational, financial, and operational performance.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…Mail et al (2006), Biancone et al (2019) and Janka et al (2020) discuss the importance of studying change management accounting practice that could lead to improve organizational innovation and performance. Mail et al (2006) demonstrated that management accounting, as a managerial tool in creating organizational control, has a positive effect on organizational, financial, and operational performance. Traditionally, MCI's jurisdiction has played a role in providing information to assist managers in decision-making (Kaplan & Norton, 1996).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim is to investigate the performance of the EFCC and to identify how institutional and organizational factors influence the effectiveness of the EFCC. This process cannot be assumed but explained and interpreted by the organizational members within the context in which EFCC operates (Mail et al, 2006).…”
Section: The Process Of Data Collection and Analysismentioning
confidence: 99%